Manajemen Pengawasan Kepala Madrasah dan Kinerja Guru dalam Meningkatkan Sikap Religiusitas Peserta Didik - Ahmad Jaelani (Universitas Islam Kiai Haji Achmad Siddiq Jember, 2020)
Religiosity attitude of students so far has not received enough attention in an educational institution. Educators or teachers are still preoccupied with various administrative tasks so that the performance of teachers as educators who are supposed to provide education to students is neglected. Especially religious education which provides a change in the attitude of religiosity of students. Religiosity attitude of students is still low. Allegedly because the performance of teachers and madrasah head supervision is not optimal. This study aims to determine the supervision management of madrasa principals and teacher performance in improving the religiosity of students in Madrasah Aliyah Darul Ulum Sukaraja, Garut Regency. The study uses a qualitative approach with primary data obtained from observations and interview results. The results obtained were the supervision of the madrasa headmaster and the teacher's performance carried out well, optimally and effectively so that the students' religiosity attitude increased. These findings reinforce the opinion of Komariah and Mulyati (2009) in Encu (2012: 9) that good and effective supervision is obtained from four aspects, namely: (1) setting performance standards, 2) measuring performance, 3) comparing performance with predetermined standards, 4) take corrective action when a deviation is detected. While the indicators of supervision carried out by a leader in this case are the headmaster of a madrasa, namely: a) setting targets and limits of work, b) defining common goals clearly, c) turning ideas into reality, d) supervising during program realization. Sikap religiusitas peserta didik selama ini masih kurang mendapat perhatian pada sebuah lembaga pendidikan. Pendidik atau guru masih disibukkan dengan berbagai tugas administrasinya sehingga kinerja guru sebagai pendidik yang seharusnya memberikan pendidikan kepada peserta didik menjadi terbengkalai. Terutama pendidikan agama yang memberikan perubahan terhadap sikap religiusitas peserta didik. Sikap religiusitas peserta didik masih rendah. Diduga karena kinerja guru dan pengawasan kepala madrasah yang belum optimal. Penelitian ini bertujuan untuk mengetahui manajemen pengawasan kepala madrasah dan kinerja guru dalam meningkatkan religiusitas peserta didik di Madrasah Aliyah Darul Ulum Sukaraja Kabupaten Garut. Penelitian menggunakan pendekatan kualitatif dengan data primer yang diperoleh dari observasi dan hasil wawancara. Hasil penelitian yang diperoleh adalah manajemen pengawasan kepala madrasah dan kinerja guru dilaksanakan dengan baik, optimal dan efektif sehingga sikap religiusitas peserta didik meningkat. Hasil temuan ini memperkuat pendapat Komariah dan Mulyati (2009) dalam Encu (2012:9) bahwasanya pengawasan yang baik dan efektif itu diperoleh dari empat aspek, yaitu: (1) menetapkan standar kinerja, 2) mengukur kinerja, 3) membandingkan unjuk kinerja dengan standar yang telah ditetapkan, 4) mengambil tindakan korektif saat terdeteksi penyimpangan. Sementara indikator dari pada pengawasan yang dilakukan oleh seorang pemimpin dalam hal ini adala kepala madrasah yaitu: a) menentukan target dan batasan kerja, b) menentukan tujuan bersama dengan jelas, c) mewujudkan gagasan menjadi kenyataan, d) melakukan pengawasan pada saat realisasi program. Kata Kunci: manajemen pengawasan kepala madrasah, kinerja guru, religiusitas peserta didik